Determination of Biological Activities of Cardopatium corymbosum L. against Food Pathogens - Gulten Okmen; Ridvan Tekin; Irem Camur; Kutbettin Arslan; Busra Eroglu (Turkish Journal of Agriculture: Food Science and Technology)
Food spoilage pathogens threaten to human health. In this work was studied biological activity of plant known as the “kurtludiken” in Turkey and it is contributed to the literature. Cardopatium corymbosum L. from Mugla region were collected for antimicrobial and antioxidant activity studies. The antimicrobial activity studies were done by disc diffusion method. A total of 8 microorganisms were used at this study, one of them is yeast and the others are bacteria. The 2,2′-azinobis-(3 ethyl benzothiazoline-6-sulfonic acid) (ABTS•+) was used for non-enzymatic antioxidant activity experiments. There are few studies on the biological activities of Cardopatium corymbosum. The aim of this study is to determine the antimicrobial and antioxidant effects of Cardopatium corymbosum against food pathogens. The radical scavenging percentage of plant was found to be 13%. As a result, Cardopatium corymbosum have antimicrobial and antioxidant capacities.